Application of BS 7910 to high pressure pipelines. (December 2018) - Andrews, Robert; Cosham, Andrew; Macdonald, Kenneth
Highlights: Characteristics of high pressure steel pipelines that are relevant to use of BS 7910 are reviewed. Issues when assessing fracture of axial and circumferential cracks in pipelines are described. Alternative approaches from other standards compared to those of BS 7910. Suggestions made for improvements in the next edition of the standard.